COVID-19 Mortality and Morbidity Rate in a Tertiary Care Hospital Swat, Pakistan - Tabbassum Imran, Najeeb Ullah, Fazal Hanan, Waseem Khan, Abid Ul Ghafoor, Amreek Lal, Imtiaz Ahmad, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Because of the recent outbreak of Covid-19, the globe is now facing a number of difficult challenges. The morbidity and mortality rate varies depending upon numerous factors. Objective: The objective of the study was to find out the mortality and morbidity rate of Covid-19 in a tertiary care hospital of Swat Methodology: This descriptive cross-sectional study was carried out at the Department of Pathology, Swat Teaching Hospital, Swat, Khyber Pakhtunkha Pakistan for duration of one year from April 2020 to March 2021. Nasopharyngeal or Oropharyngeal swabs were taken from all the enrolled patients and sent to the national institute of health Islamabad or swat public health laboratory for the diagnosis of Covid-19. The rate of morbidity and mortality for all the enrolled patients was recorded. All the data analysis was done by using IBM SPSS version 23. Results: In the current study, totally 11609 patients were enrolled. There were 7329 (63.13%) males and 4280 (36.87%) females. The overall morbidity rate of covid-19 was 18.25% (n= 2089) whereas the overall mortality rate was13.16% (n=275) patients. Conclusion: Our study concludes that the rate of morbidity and mortality of covid-19 is high in district Swat Khyber Pakhtunkhwa, Pakistan. The burden of covid-19 was high in males as compared to females and the mortality rate increases with the increase in age. All the people residing in the district Swat should be vaccinated to decrease both the morbidity and mortality rate of covid-19. Keywords: Covid-19; Mortality; Morbidity; Swat